2008
DOI: 10.1176/appi.ajp.2007.07050740
|View full text |Cite
|
Sign up to set email alerts
|

Infections in the CNS During Childhood and the Risk of Subsequent Psychotic Illness: A Cohort Study of More Than One Million Swedish Subjects

Abstract: Serious viral CNS infections during childhood appear to be associated with the later development of schizophrenia and nonaffective psychoses. The association with specific viruses suggests that the risk is related to infectious agents with a propensity to invade the brain parenchyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
1
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(144 citation statements)
references
References 41 publications
6
128
1
9
Order By: Relevance
“…Causes of HI in young people that may also have an impact on the risk for psychotic experiences include birth trauma (Herrgard et al 1995) and prenatal and postnatal exposure to infections (Dalman et al 2008 ;Zammit et al 2009). Rubella and meningitis may harm the developing central nervous system, and exposure has been associated with an increased risk for both hearing deficits (Fortnum & Davis, 1993) and psychosis (Brown et al 2000 ;Leask et al 2002 ;Dalman et al 2008). Thus, HI and psychosis may be the result of a single underlying causative mechanism.…”
Section: Hi and Psychosis : A Shared Cause ?mentioning
confidence: 99%
See 1 more Smart Citation
“…Causes of HI in young people that may also have an impact on the risk for psychotic experiences include birth trauma (Herrgard et al 1995) and prenatal and postnatal exposure to infections (Dalman et al 2008 ;Zammit et al 2009). Rubella and meningitis may harm the developing central nervous system, and exposure has been associated with an increased risk for both hearing deficits (Fortnum & Davis, 1993) and psychosis (Brown et al 2000 ;Leask et al 2002 ;Dalman et al 2008). Thus, HI and psychosis may be the result of a single underlying causative mechanism.…”
Section: Hi and Psychosis : A Shared Cause ?mentioning
confidence: 99%
“…First, HI and psychosis may be the consequence of a common underlying cause. For example, exposure to perinatal infections affecting the central nervous system, such as rubella and meningitis (Brown et al 2000 ;Leask et al 2002 ;Dalman et al 2008), may explain the association between early HI and later psychosis. Second, psychotic experiences may be a direct or indirect consequence of processes triggered by hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that infections and autoimmune diseases are clin ic ally important risk factors for the development of schizo phrenia. [1][2][3] Furthermore, a recent study integrating results from a meta analysis of genome wide association studies in schizophrenia found that the most significant changes were observed in genetic loci related to the immune system. 4 Also, patients with schizophrenia show microglial activation, as re vealed by positron emission tomography.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been suggested that central nervous system infections of cytomegalovirus or mumps virus in childhood may also increase the risk for schizophrenia (Dalman et al, 2008). All of these factors have been shown to affect mitochondria, inducing strong intracellular oxidative stress and/or apoptosis (Akaike et al, 1990;Edlund et al, 1994;Speir et al, 1998;He et al, 2003;Berger et al, 2004;Zaki et al, 2005;Gupta et al, 2004;Kruman et al, 2006;Wang et al, 2006;Poncet et al, 2006;Chang et al, 2007;Nishikawa et al, 2007).…”
Section: Prenatal Risk Factors For Schizophreniamentioning
confidence: 99%